MAKNA EMOTIF DALAM DEBAT PUBLIK PUTARAN PERTAMA PASANGAN CALON WALIKOTA DAN WAKIL WALIKOTA SOLOK TAHUN 2020 - Zona Rida Rahayu (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2022)
Debate activities can also involve emotions. In linguistics, conveying the meaning of speech contains an element of emotion called emotive meaning. For this reason, the meaning of emotive is studied in the first round of public debates for the candidates for Mayor and Deputy Mayor of Solok in 2020. This study uses a qualitative approach and descriptive method to explain the emotive meaning used by pairs of candidates in debating. The emotive meaning studied is influenced by phonetic factors, slogans, emotive derivation, evaluation elements, emotive values, and evocative values. Of these six emotive meanings, the evaluation element that often appears is used by speakers in debating. This is because, the speaker gave an assessment of the previous leadership's performance related to all infrastructure fields in Solok City. The purpose of the speaker to bring up the evaluation element in his speech is to stand out, provide information, give the speaker strength, so that the people of Solok City can choose to replace the previous leadership position.